Spatial differentiation and influencing factors of effective phosphorus in cultivated soil in the water source area of the mid-route of South-to-North water transfer project - Wu, Zhengxiang; Zhou, Yang; Wang, Miao (Frontiers in Microbiology, 2024)
The long-term application of phosphate fertilizers in agricultural production leads to a large accumulation of phosphorus in the soil, when it exceeds a certain limit, phosphorus will migrate to surrounding water bodies through surface runoff and other forms, which can easily cause environmental risks such as eutrophication of water bodies and increase the hidden danger of water source pollution.This study take Shiyan City, the water resources area of the mid-route of the South-to-North Diversion Project (MSDP), as the study area, based on 701 sampling points of topsoil, geostatistics and geodetectors were used to explore the spatial heterogeneity and influencing factors of available phosphorus (AP) in the topsoil of the area. The results show that the effective phosphorus content in the topsoil of the study area range from 0.30 to 146.00 mg/kg, with an average value of 14.28 mg/kg, showing strong variability characteristics. Geostatistical analysis shows that among all theoretical models, the exponential model has the best fitting effect, with a lump gold effect of 0.447 and a range of 82000m. The soil available phosphorus content shows a increasing trend from the central valley lowlands to the surrounding mountainous hills. Among them, elevation is the main controlling factor for the spatial variation of available phosphorus in the topsoil, next are soil types, planting systems, annual precipitation and organic matters. The non-linear enhancement or dual factor enhancement between various environmental factors reveals the diversity and complexity of spatial heterogeneity influencing factors of available phosphorus content in cultivated soil. This study could provide scientific reference for the maintenance of ecological security in the water source area of the MSDP, improvement of precise management of AP and cultivated land quality.